THE SHIFT OF NON-PROFIT CONTRACT TO BUSINESS CONTRACT IN THE ISLAMIC FINANCIAL INSTITUTION BUSINESS ACTIVITIES - Muhammad Maksum; M. Asrorun Niam Sholeh; Yayuk Afiyanah (Universitas Islam Negeri Mataram, 2020)
This article examines the shift of contract objectives from what originally set for non-profit objectives to business ones. Such shift is found in the three contracts; wakalah (power of attorney), hawalah (underground banking), and kafalah (guarantee). Referring to their uses in several Islamic financial products in Indonesia and comparing to the sharia resolution of Sharia Authority Council Malaysia and Islamic law (fiqh), the majority of these contracts is proven to apply fees (ujrah) and used both independently and in combination with other contracts. Here, the fees are mostly applied in the Islamic financial institutions, but unfortunately the customers who are involved in the contracts get less. This, in turn, affects and changes the contract classification which originally included the three in the non-profit contract and eventually turns them into the business contract. If the contracts are set for business objectives, they are then considered as service/lease based contracts (ijarah). In the construction of a real agreement (contract), this shift has implications on changes in the rights and responsibilities of the parties involved and can raise a dispute cause of misunderstanding of the status of the contract as voluntary (tabarru’) or business (tijari).